Encounter with Meister Eckhart in the 21st Century - Lapoujade, María Noel (2025)
This paper focuses on several of the main aspects of J. Eckhart thinking from the insight of a XXI century philosopher. The main purpose is exploring the fundamental contributions of Eckhart´s mystic philosophy, emphasizing in his language, teaching, logic, ethics, onthology, subjects that manifest the character of a philosophy in movement. In these aspects emerge the originality in the integration of diverse philosophies of the Tradition, as well as the novelty of his absolutely relevant thinking. In the same way it comprehends the relationship of thought with other very distinct philosophers from diverse epoques. The investigation takes in consideration the inquiry of primary sources, such as Treatises and Sermons of Meister Eckhart. The interpretation extends on a double way: the ascendant way that goes from human condition to mystic union. its stages go from detachment to emptiness in which you conquer the liberty of the without a why, the road that make possible to be near of the mystic union, and a second stage: the descendant way that take us to God, the emanation, the nature and creation of Nature, the human creation, the being.